Relationship of social support system to the level of self-care capability among the elderly at Sta. Fe, Leyte - Mangada, Miguel E. (1997)
The descriptive-association research, conducted from April to May 1996, aimed to investigate the relationship between social support system and the level of self-care capability among the elderly in Sta. Fe, Leyte. The study, with 221 elderly as respondents revealed the following results: (1) 131 or 59.27of the sample are within the age range 60-69 years old; there were more women (65.16) than men (34.84); 49.32were married and 47.06were widowed; 67.42finished the elementary level of education while 10never went to school; and, 43have income less than P20,000.00 per annum while 40have no income at all; (2) majority of the respondents (70 to 90) could perform all the self-care activities at a high level of capability; (3) less than 50were dependent on others for food, housing and financial needs; more than 50were independent with respect to clothing and transport provisions; their emotional need for love comes principally from primary sources (62.88) while the need for praise comes mostly from secondary sources (64.70); more than 60felt that they were respected by immediate members of the family, distant kins, friends as well as by the community; about 48were getting informational support from primary and secondary sources; 18received spiritual support from primary and secondary sources.Majority of those who received instrumental, emotional , informational and spiritual support felt that the supports were adequate. These types of support were correlated to the elderly's level of self-care capability. Results of the gamma correlational analysis indicated association only between perceived degree of adequacy in emotional support and level of self-care capability (G=0.6064); Z value 1.96). This result confirms that since the elderly have a positive view of themselves in terms of love from their immediate families, respect and praise from others outside their families, they are able to perform self-care activities at the highest possible level.Data from the study can guide policy makers and implementors on what socio-economic programs can be adopted to enhance the self-care capability of the elderly. The different implementors of the programs namely the church, academe, NGOs and philanthropic organizations may be tapped and encouraged to embark on affirmative action programs such as proper attitude in the care of the elderly.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Aged -- Social networks; Aged -- Care; Elderly. -- Support system